2011
DOI: 10.4183/aeb.2011.337
|View full text |Cite
|
Sign up to set email alerts
|

Gnagliosides and Sex Hormones in Human Melanoma

Abstract: Background. Malignant melanoma is the most aggressive form of skin cancer with a rapidly increasing incidence rate. In contrast to other tumors, the role of sex steroid hormones in the initiation and progression of melanoma remains unclear.Objective. To assess the interaction between the content and composition of gangliosides and sex steroid hormones 17βestradiol (E2) and testosterone (T) in malignant melanoma.Patients and methods. The analysis included 45 melanoma patients (age 28-86; 14 men, 15 non -pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…Based on this analysis, the authors found that low levels of circulating gangliosides are positive prognosis factors, in terms of increasing the relapse free survival in patients with malignant melanoma. These results justify the role of serum gangliosides as potential biomarkers in the management of patients with melanoma, a finding that supports previous researches [10,11,53,102,103].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Based on this analysis, the authors found that low levels of circulating gangliosides are positive prognosis factors, in terms of increasing the relapse free survival in patients with malignant melanoma. These results justify the role of serum gangliosides as potential biomarkers in the management of patients with melanoma, a finding that supports previous researches [10,11,53,102,103].…”
Section: Discussionsupporting
confidence: 77%
“…New research directions developed in order to discover markers for early detection and therapeutic response of melanoma, treatments that could improve the survival rate. Recent studies showed that melanoma is a heterogeneous group of complex molecular disorders [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. The diversity of these alterations sustain the importance of, on one hand, an individualized diagnosis, prognosis and treatment of melanoma patients, and, on the other hand, the detection of new biomarkers and therapeutic approaches in these patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All data were evaluated using EpiInfo 2008. Details about the structure of the gangliosides used in this study were presented before (12).…”
Section: Discussionmentioning
confidence: 99%
“…Gangliosides are a group of bioactive glycolipids, located on the outer face of cell membranes. These glycolipids play a major role in cell proliferation, differentiation, migration, apoptosis, signal transduction, cell adhesion, modulating growth factor or hormone receptor, antigen recognition, protein trafficking, viral transformation, and oncogenesis [1][2][3][4][5]. Atypical expression of some ganglioside antigens associated with certain tumours (neuroblastomas, melanomas, gliomas, lymphomas, small cell lung cancer, and prostate cancer) and furthermore could play an important role in cancer immunotherapy [6][7][8].…”
Section: Introductionmentioning
confidence: 99%